Egodokumentalne ślady człowieka w Internecie i ich archiwizacja - Konopa, Bartłomiej; Rosa, Agnieszka (Archeion (Warszawa), 2023)
The primary goal of the article is to present the issues of born digital sources, which have the characteristics of generic egodocuments, and the issues of their archiving. These sources contain traces related to human presence and actions in the form of text or text with images and give the researcher the opportunity to learn about the emotions, experiences, sensitivity, and personal life of their creator. The authors of the article are therefore looking for answers to the questions of whether people leave ego-documents on the Internet in the form of their traces or products, what type of sources they are, whether their archiving is possible and how it is carried out, whether archived sources are available to researchers, and then whether it is possible to use them in egodocumentary research. Ultimately, the authors decided that, due to the contributing nature of the article, two types of human creations on the Internet would be taken into account, i.e., personal home websites and blogs. Their ego-documentary nature was pointed out. Attention was also paid to the archiving processes of this part of the Web and the problems associated with them, in particular archiving methods and strategies and legal, technical, and ethical limitations. Then, issues related to access to archived resources were discussed, where two issues play a significant role: the openness of the archive and methods of searching its resources. The authors also cited selected scientific research, aiming to show the possibility of using archived Web egodocuments in research. The article uses the analysis of texts and research on the theory of egodocument and Web archiving, but above all, the comparative method, reconceptualization of the definition of egodocument, as well as the definition of digital traces defined as egodocumentary wholes — that is, born digital sources that, when archived, enable researchers of the past using text analysis (and not binary codes) to learn about the creator’s personality and life.